2007
DOI: 10.1158/1078-0432.ccr-07-0332
|View full text |Cite
|
Sign up to set email alerts
|

Selecting Patients for Treatment with Epidermal Growth Factor Tyrosine Kinase Inhibitors

Abstract: Identification of objective tumor regressions with epidermal growth factor receptor tyrosine kinases (EGFR TKI) in non^small cell lung cancer (NSCLC) patients has resulted in intense, worldwide clinical and basic research directed toward finding the optimal use of EGFR TKIs in NSCLC. EGFR TKI clinical trials have shown that higher response rates and longer survival are associated with specific patient characteristics and that using conventional chemotherapy simultaneously with EGFR TKIs in unselected patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 48 publications
1
46
0
Order By: Relevance
“…EGFR amplification, preferentially of a mutant allele, is correlated with but does not reliably predict EGFR overexpression [17]. Mutations in the EGFR gene are rare in colorectal cancer but occur regularly in other cancer types, such as lung cancer [18][19][20][21].…”
Section: Egfr and Colorectal Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…EGFR amplification, preferentially of a mutant allele, is correlated with but does not reliably predict EGFR overexpression [17]. Mutations in the EGFR gene are rare in colorectal cancer but occur regularly in other cancer types, such as lung cancer [18][19][20][21].…”
Section: Egfr and Colorectal Cancermentioning
confidence: 99%
“…For these reasons, EGFR mutations have limited to no prognostic power and also do not predict EGFR-targeted treatment outcomes in patients with colorectal cancer [19]. In non-small-cell lung cancer, however, EGFR mutations and gene amplification are closely linked with favorable response to small-molecule tyrosine kinase inhibitors [18,20,21,36]. Of note, a recent study reported a strong correlation between EGFR mutation status and phosphorylation of the EGFR at tyrosine 992 (pEGFRtyr992) as detected by IHC [37].…”
Section: Egfr and Colorectal Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Although some studies have suggested that EGFR mutations are prognostic rather than being predictive factors (Eberhard et al, 2005;Shepherd and Tsao, 2006), many have shown that they are in fact predictive of favorable clinical outcomes with EGFR TKIs (Bonomi et al, 2007) (see the article by Gazdar (2009) within this issue for a full review of this topic). In four separate studies of EGFR TKIs in patients with metastatic NSCLC, a significantly longer OS was observed in patients harboring EGFR mutations (Cortes-Funes et al, 2005;Han et al, 2005;Mitsudomi et al, 2005;Takano et al, 2005).…”
Section: Prognostic Versus Predictive Biomarkersmentioning
confidence: 99%
“…A major advance for a patient selection with the objective to draw greater benefits from a combination between anti-EGFR drugs and conventional chemotherapeutic agents comes from the tumour determination of EGFR and K-Ras mutational status. In lung cancer patients, molecular studies have revealed that EGFR-activating mutations are frequently found in patients who have the best outcomes with EGFR TKIs combined with conventional chemotherapy (Bonomi et al, 2007). Several groups from Europe and the United States have reported that the absence of K-Ras mutation was a condition necessary to obtain a clinical response to the association between cetuximab and irinotecan in irinotecan refractory patients (LiĂšvre et al, 2008).…”
Section: A Ray Of Hopementioning
confidence: 99%